Pemanfaatan Lahan Terlantar Dalam Upaya Mendukung Ketahanan Pangan Tinjauan Hukum Positif Indonesia dan Hukum Islam - Natasha, Mike Indah, Mutimatun Ni'ami, S.H., M.Hum, Darsono, S.H., M.Hum (2016)
In this writing, I am linking abandoned land for the sake of food security. Indonesia as a country that is called an agrarian country it's not able to meet all the food needs of the Indonesian people. Indonesia is big enough to import food items which impact on price fluctuations the food. One solution could be offered in support of food security is by utilizing the existing land abandoned well. Research purposes, first, to know the management of food security related land abandoned by Indonesian laws. Second, to know the management of abandoned land related food security according to Islamic law. This study uses normative doctrinal approach is data obtained were analyzed based on the applicable law in Indonesia. According to the Indonesian positive law, the management of abandoned land in the hands of the National Land Agency, while according to Islamic law abandoned land management is highly recommended by anyone who wants to manage or in Islam is also called the Ihya 'al-Mawat, in some way mukharabah or muzara'ah. Keywords: Abandoned land, Food security, Ihya'al-mawat